Outreach programmes for health improvement of Traveller Communities: a synthesis of evidence - Susan M Carr; Monique Lhussier; Natalie Forster; Deborah Goodall; Lesley Geddes; Mark Pennington; Angus Bancroft; Jean Adams; Susan Michie (NIHR Journals Library, 2014)
Background: The term 'Traveller Communities' refers to a complex population group encompassing Romani Gypsies, Irish Travellers, Welsh Travellers, Scottish Travellers, Roma, New Travellers, Travelling Showpeople, Circus People and Boat Dwellers. A lack of reliable demographic data combined with nomadic lifestyles leads to potential invisibility in health service planning and results in unmet needs.Outreach has been utilised as a key strategy to engage Traveller Communities in health improvement interventions. Aim: To synthesise the evidence on outreach programmes to improve the health of Traveller Communities. Design: Scoping, economic and realist reviews were employed with the following objectives: (1) to quantify and classify the evidence concerning Traveller Communities' health; (2) to estimate the costs of different types of outreach and determine which might be considered cost-effective and (3) to develop explanations of how, for whom and in what circumstances outreach works best. Methods: Comprehensive searches of electronic databases and grey literature were undertaken using a broad search strategy to identify publications relevant to Traveller Communities and health. The following databases were searched: Web of Knowledge, MEDLINE, The British Library's Electronic Table of Contents (Zetoc), Cumulative Index to Nursing and Allied Health Literature (CINAHL), Applied Social Sciences Index and Abstracts (ASSIA), Social Services Abstracts, British Humanities Index, PsycArticles, Allied and Complementary Medicine Database (AMED), ProQuest Nursing and Allied Health Source, International Bibliography of the Social Sciences (IBSS) and Sociological Abstracts. Searches were conducted between August 2011 and November 2011. No restrictions on inclusion were imposed according to type of journal, publication date (up to the date of searching) or country of research or practice. Foreign-language publications were excluded. This formed a core literature base to be drawn on by the different arms of thereview. Expert hearings involving Traveller Community members and outreach workers were also undertaken to refine and validate emerging findings. Findings: Two hundred and seventy-eight articles were included in the scoping review, which highlighted the emergent nature of the evidence on outreach interventions for Traveller Communities. While much research describes the needs of Traveller Communities, as yet there has been little response to this in the form of discussion and evaluation of outreach and other interventions that might improve their health. From an economic perspective, the data available suggest that the cost of providing mobile services to travellers is high; improving accessibility of services and signposting Traveller Communities is cheaper and may be equally effective. The realist synthesis generated an explanatory framework of why outreach might lead to certain outcomes depending on the particular circumstances. The extent to which workers are trusted by the Community and whether or not the intervention focus is negotiated both have clear impacts on intervention success. Individuals engage differentially with outreach interventions, leading to participation, behaviour change or social capital improvement outcomes. Conclusions: Outreach workers need clarity about the purpose of their intervention, in terms of degrees of engagement (leading to the three outcome categories above). Where outreach aims to promote attendance at one-off events such as screening, the worker may not need to have long-established links with the Community. Changing behaviour or developing social capital, on the other hand, is a challenge that needs to build explicitly on long-established, trusting relationships. Any flexibility built into the intervention in terms of negotiating intervention topic can contribute significantly to the outcome. While true engagement with an issue must not be assumed from participation at an event, these events can be used as part of longer-term trust-building strategies. These synthesis approaches offer maximum translational potential for other marginalised groups. There is a need for more theoretically informed evaluations of engagement initiatives, in order to develop transferable lessons around how and for whom interventions work in different contexts. Further research is needed to test the explanatory potential of the framework in other socially excluded groups. Funding: The National Institute for Health Research Public Health Research programme.